Voltage‐gated proton (Hv1) channels, a singular voltage sensing domain. Issue 22 (18th August 2015) - Castillo, Karen; Pupo, Amaury; Baez-Nieto, David; Contreras, Gustavo F.; Morera, Francisco J.; Neely, Alan; Latorre, Ramon; Gonzalez, Carlos
Abstract : The main role of voltage‐gated proton channels (Hv 1) is to extrude protons from the intracellular milieu when, mediated by different cellular processes, the H + concentration increases. Hv 1 are exquisitely selective for protons and their structure is homologous to the voltage sensing domain (VSD) of other voltage‐gated ion channels like sodium, potassium, and calcium channels. In clear contrast to the classical voltage‐dependent channels, Hv 1 lacks a pore domain and thus permeation necessarily occurs through the voltage sensing domain. Hv 1 channels are activated by depolarizing voltages, and increases in internal proton concentration. It has been proposed that local conformational changes of the transmembrane segment S4, driven by depolarization, trigger the molecular rearrangements that open Hv 1. However, it is still unclear how the electromechanical coupling is achieved between the VSD and the potential pore, allowing the proton flux from the intracellular to the extracellular side. Here we provide a revised view of voltage activation in Hv 1 channels, offering a comparative scenario with other voltage sensing channels domains.